PENGGALIAN KARAKTERISTIK PENGGUNA PADA FASE ELISITASI PERANGKAT LUNAK MENGGUNAKAN USER PERSONA - Selma Osa Rohimah; Wahyu Andhyka Kusuma; Rafiatul Husna (LPPM STMIK STIKOM Indonesia, 2021)
Requirements elicitation is activities aimed at finding the needs of a system through communication with system users. The purpose of requirements elicitation is to find out what problems have been encountered. User persona is a fictional representation of the ideal user. The software developer will begin the design process by conducting user research, establishing communication with the target user and identifying exactly what they need with the product to be made. Personas are generally based on these users and combine the needs, goals, and behavior patterns observed from the target audience. This study aims to determine information systems related to the characteristics and needs of users of the software, so that the data generated in the form of qualitative data from prospective users. By using the hypotheses that are made, which will later be analyzed and used as a basis for developing projects. The results of this study are information in accordance with user needs that will be implemented using a use case and software prototype.